Hazrat zul kifal (a.s) or hazrat his queel (a.s) - Safdar shaheen (Ferozsons (PVT) LTD Lahore)
"Hazrat Zul-Kifl (A.S) aur Hazrat His-Qeel (A.S)" explores the lives and virtues of these two revered figures in Islamic history, highlighting their unwavering faith, patience, and devotion to justice in the face of trials and adversity.